Enhancing Digital Literacy in Local Communities Through Technology-Based Training - Rizky Mahendra Putra; Daniel K. Osei (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Digital literacy has become a critical requirement for social inclusion, economic participation, and access to public services. Local communities, particularly in rural and semi-urban areas, continue to experience significant digital skill gaps. This study aims to analyze the effectiveness of technology-based training programs in enhancing digital literacy in local communities. The research employed a systematic literature-based empirical analysis of community service and intervention studies published between 2014 and 2025. Data were drawn from national and international peer-reviewed journals focusing on digital literacy training, community empowerment, and technology adoption. The findings indicate that structured training programs significantly improve digital competencies, including basic computer skills, internet usage, digital security awareness, and e-commerce engagement. Programs that integrate participatory learning, cultural relevance, and hands-on practice demonstrate higher effectiveness and sustainability. The study also identifies key success factors, such as local facilitator involvement, contextualized content, and continuous mentoring. These findings contribute to the development of an evidence-based framework for designing effective digital literacy interventions at the community level. The study concludes that technology-based training is a practical and scalable approach to reducing the digital divide and strengthening community resilience in the digital era.